The role of the SLC6A3 3’ UTR VNTR in nicotine effects on cognitive, affective, and motor function - Schröder, Rebekka; Reuter, Martin; Faßbender, Kaja; Plieger, Thomas; Poulsen, Jessie; Lui, Simon S. Y.; Chan, Raymond C. K.; Ettinger, Ulrich (Psychopharmacology, 2022)
Rationale Nicotine has been widely studied for its pro-dopaminergic effects. However, at the behavioural level, past investigations have yielded heterogeneous results concerning effects on cognitive, affective, and motor outcomes, possibly linked to individual differences at the level of genetics. A candidate polymorphism is the 40-base-pair variable number of tandem repeats polymorphism (rs28363170) in the SLC6A3 gene coding for the dopamine transporter (DAT). The polymorphism has been associated with striatal DAT availability (9R-carriers > 10R-homozygotes), and 9R-carriers have been shown to react more strongly to dopamine agonistic pharmacological challenges than 10R-homozygotes. Objectives In this preregistered study, we hypothesized that 9R-carriers would be more responsive to nicotine due to genotype-related differences in DAT availability and resulting dopamine activity. Methods N =194 non-smokers were grouped according to their genotype (9R-carriers, 10R-homozygotes) and received either 2-mg nicotine or placebo gum in a between-subject design. Spontaneous blink rate (SBR) was obtained as an indirect measure of striatal dopamine activity and smooth pursuit, stop signal, simple choice and affective processing tasks were carried out in randomized order. Results Reaction times were decreased under nicotine compared to placebo in the simple choice and stop signal tasks, but nicotine and genotype had no effects on any of the other task outcomes. Conditional process analyses testing the mediating effect of SBR on performance and how this is affected by genotype yielded no significant results. Conclusions Overall, we could not confirm our main hypothesis. Individual differences in nicotine response could not be explained by rs28363170 genotype.